Morphometric and Meristic Characteristics of Freckled Goatfish (Upeneus tragula) from Madura Strait, East Java - Santanumurti, Muhammad Browijoyo; Hartono, Sugeng; Alim, Muhammad Bachrun (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
The kuniran fish or goatfish, from genus Upeneus, is the most commonly found species in the world from the Mullidae family. This study aims to provide information regarding the morphological characteristics of Upeneus from the Madura Strait. The method used in this study is the survey method. This study was conducted in June 2023 in the Madura Strait (East Java, Indonesia). The parameters tested for the morphological identification of Upeneus fish are morphometric and meristic tests. Fish morphometric tests are quantitative measurements and analyses of the shape and size of fish body parts to identify fish species in terms of length or weight. Meanwhile, meristic tests are recording and analyzing the number of fish body structures that can be counted, such as the number of scales, fin rays, or certain bones. The results show that the kuniran fish/goatfish or Upeneus found in the Madura Strait was U. tragula which had the main morphometric characteristics of 17 cm SL, with a head length of 25.88, a head depth of 18.82, and a snout length of 5.88. This fish had two dorsal fins, one ventral fin, two pectoral fins, one anal fin, and a caudal fin. The ventral and anal fins were yellow, with a brownish-white caudal fin. In this study, U. tragula had meristic characteristics of VIII dorsal fin spines, 10 dorsal fin rays, 34 caudal fin rays, III + 6 anal fin rays, and 12 pectoral fin rays.